The serum IgG antibody level as a biomarker for clinical outcome in patients with cerebral sparganosis after treatment - Xiang, Haijie; Wang, Jie; Tan, Dandan; Xiong, Ying; Huang, Pengcheng; Shen, Yu; Xu, Yun; Gong, Zhihong; Hu, Fei; Xu, Chunhua; Wu, Jie; Liu, Wei; et al. (Frontiers in Immunology, 2023)
Cerebral sparganosis is a rare parasitic infection of the brain tissue. The remission of MRI change and clinical symptom has been used to evaluate the therapeutic effect. However, there is no study to correlate the serum IgG antibody level of sparganum to the prognosis of disease after treatment. In this study, we collected 87 patients with cerebral sparganosis from three medical centers. Clinical symptoms and MRI changes were evaluated at 12 months after initial treatment, and serum IgG antibody level of sparganum was evaluated at 2, 6, and 12 months after treatment. The positive cut-off value was based on 2.1 times the optical density (OD) of negative control. The index value was defined as the sample OD divided by the cut-off value. Among the 87 patients after treatment, 71 patients had good clinical outcomes, and 16 had poor clinical outcomes. The area under the curve (AUC) showed that the index value measured at 12 months after treatment had the best prediction effect, with a value of 2.014. In the good-outcome group, the index values were less than 2.014 in all 71 patients, and only 8 patients had mildly enhanced residual lesions on MRI. In the poor-outcome group, the index values were more than 2.014 in all 16 patients, and all patients still showed significantly enhanced lesions on MRI. Compared with poor-outcome patients, only 2 patients with good outcomes had disease recurrence after treatment. Collectively, the serum IgG antibody level of sparganum was a promising biomarker to evaluate the prognosis of patients with cerebral sparganosis after treatment.